Direct determination of molecular weight distribution of calf‐thymus DNAs and study of their fragmentation under ultrasonic and low‐energy infrared irradiations. A charge detection mass spectrometry investigation. (5th August 2018) - Halim, Mohammad A.; Bertorelle, Franck; Doussineau, Tristan; Antoine, Rodolphe
Abstract : Rationale: Calf‐thymus (CT‐DNA) is widely used as a binding agent. The commercial samples are known to be "highly polymerized DNA" samples. CT‐DNA is known to be fragile in particular upon ultrasonic wave irradiation. Degradation products could have dramatic consequences on its bio‐sensing activity, and an accurate determination of the molecular weight distribution and stability of commercial samples is highly demanded. Methods: We investigated the sensitivity of charge detection mass spectrometry (CDMS), a single‐molecule MS method, both with single‐pass and ion trap CDMS ("Benner" trap) modes to the determination of the composition and stability (under multiphoton IR irradiation) of calf‐thymus DNAs. We also investigated the changes in molecular weight distributions in the course of sonication by irradiating ultrasonic waves to CT‐DNA. Results: We report, for the first time, the direct molecular weight (MW) distribution of DNA sodium salt from calf‐thymus revealing two populations at high (~10 MDa) and low (~3 MDa) molecular weights. We evidence a transition between the high‐MW to the low‐MW distribution, confirming that the low‐MW distribution results from degradation of CT‐DNA. Finally, we report also IRMPD experiments carried out on trapped single‐stranded linear DNAs from calf‐thymus allowing extraction of their activation energy for unimolecular dissociation. Conclusions: We show that single‐pass CDMS is a direct, efficient and accurate MS‐based approach to determine the composition of calf‐thymus DNAs. Furthermore, ion trap CDMS allows us to evaluate the stability (both under multiphoton IR irradiation and in the course of sonication by irradiating ultrasonic wave) of calf‐thymus DNAs.